Didactic tasks and development of language and vocational skills. The French business example - Sowa, Magdalena (Glottodidactica, 2020)
Task Based Learning / Teaching focuses on the action dimension of language use, i.e., various tasks performed every day that require cooperation with others and the mobilization of language. Language proves to be the most important instrument of action, even if the objective of this action is not necessarily linguistic. The pedagogical tasks used for language teaching for professional purposes illustrate the link between language and socio-professional action: the learning of the formal language system counts as much as the content of the domain of work. On these theoretical assumptions, the aim of this paper is to examine the degree of integration of linguistic and professional knowledge and skills into tasks designed for the teaching of business French. We will analyse the examples of pedagogical tasks in order to demonstrate to what extent they allow us to teach interdisciplinary content and foreign language.